eDoc: a documentation tool for UML based models - Lobo, Sabrina Barbirato; Oliveira, Rodrigo Fernandes de; Teles, Vinícius Manhães (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2001.24002, 2001)
The last few years have produced many improvements in software development methodologies and modeling languages. The use of Unified Software Development Process, Unified Modeling Language and Object Oriented languages has proved to be a step forward for every developer who works hard to deliver a good software. However, there is still a lot to do in terms of tools. There are already many good CASE tools as far as drawing is concerned. But it is hard to find one where drawing and documentation can be done consistently and integrated, as they should be. eDoc is a tool which can be integrated with traditional CASE tools in order to provide: visibility over the relationships among model elements, support for requirements capture, explicit linking between requirements and its correspondent use cases, use of templates for documentation, a way for the stakeholder to access the documentation, single glossary and finally consistency between diagram and document.